Optical and other solitons for the fourth-order dispersive nonlinear Schrödinger equation with dual-power law nonlinearity. (May 2017) - Al Qurashi, Maysaa Mohamed; Yusuf, Abdullahi; Aliyu, Aliyu Isa; Inc, Mustafa
Abstract: In this work, the soliton solutions of the fourth-order nonlinear Schrödinger equation (NLSE) with dual-power law nonlinearity is analyzed using Ricatti-Bernoulli (RB) sub-ODE and modified Tanh-Coth methods. We obtain new solutions that are not in existence in previous time. The constraint conditions between the soliton parameters are determined. The solutions we obtained may be used to explain and understand the physical nature of the wave spreads in the most dispersive optical medium. Highlights: We obtain some new type solitons for the fourth-order dispersive NLSE with dual power nonlinearity. Optical, singular, algebraic and periodic wave solitons are reported. We write physical properties of obtained solutions.